The Detection of Human Papilloma Virus- 16, in Oral Squamous Cell Carcinoma by in Situ Hybridization (Mustansiria Dental Journal, 2018)
Background: Squamous cell carcinoma of the oral cavity constituted a major healthproblem and can be a leading cause of death. Several studies link high risk Humanpapillomavirus -16 to oral squamous cell carcinoma as an important etiologicalfactor. Several molecular markers have also been the subject of an intenseresearch work, trying to clarify their role in oral carcinogenesis. Of these, thecancer suppresser gene P53 has been extensively studied.Aim of the study: to detect the association of the molecular markers Humanpapillomavirus -16, in the oral Squamous cell carcinoma using in situhybridization technique and To correlate Human papillomavirus -16 with clinicaldata (age, sex, risk factors grade &stage).Material & Methods: Tumor tissues from 33 patients with newly diagnosed as oralsquamous cell carcinoma & who were surgically treated collected, formalin fixed& paraffin embedded. Sections on charged slides were made from each tissueblock and submitted to in situ hybridization technique utilizing Humanpapillomavirus -16, cDNA probe.Results: Human papillomavirus -16 was localized by in situ hybridizationspecifically within the nuclei of cancer cell it was detected in (27) (81.8%) of 33oral squamous cell carcinoma patients. Most of Human papillomavirus -16positive patients were within the age group (50-59) years. However, there was nosignificant correlation between Human papillomavirus -16 positive &age. Nosignificant correlation was found to sex &risk factors (smoking &alcoholconsumption) either. Most of cases were moderately differentiated squamous cellcarcinoma (79%). however no significant correlation was detected regardinghistopathological grading or clinical staging with Human papillomavirus -16.Conclusions: Oral HPV-16 infections are strongly associated with OSCC. Amongsubject with or without the established risk factor of tobacco& alcohol use